Short Movie as Micro Counseling Learning Media during the Covid-19 Pandemic - Yuli Nurmalasari; Sujarwo Sujarwo (STAI Hubbulwathan Duri, 2022)
The research aims to develop short movies as a medium for learning micro counseling. The short movies developed illustrate the basic skills of counseling through scenes from the counselor and the counselee. The short film consists of three parts: a short movie entitled Pulih, a short movie review, and a short movie entitled 'Do's and Don'ts'. The research uses a quantitative research approach with research and development methods. The research was carried out in four stages: the preliminary stage, the planning stage, the implementation stage, and the result formulation stage. The data were obtained through the assessments given by experts and prospective users which were analyzed descriptively. The results showed that the product developed was feasible to be used as a micro counseling learning medium.